2019
DOI: 10.1007/s00167-019-05835-2
|View full text |Cite
|
Sign up to set email alerts
|

The tibial cut influences the patellofemoral knee kinematics and pressure distribution in total knee arthroplasty with constitutional varus alignment

Abstract: PurposeThe current literature suggests that kinematic total knee arthroplasty (kTKA) may be associated with better outcome scores in patients with constitutional varus alignment. The underlying patellofemoral kinematic changes (patella tilting and patella tracking) and patellofemoral pressure distribution have not yet been described. The present study compared the effects of different tibial cuts, as used in kTKA, on patellofemoral knee kinematics and the pressure distribution, in addition to comparisons with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The stippled lines indicate the 95% CIs. Short vertical lines on the x-axis represent individual case in the study the normal state [13]. Blakeney et al suggested KA-TKA reproduced more closely normal gait of healthy controls compared to MA-TKA due to the restoration of the individual's knee kinematics and ligament tension in KA-TKA [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stippled lines indicate the 95% CIs. Short vertical lines on the x-axis represent individual case in the study the normal state [13]. Blakeney et al suggested KA-TKA reproduced more closely normal gait of healthy controls compared to MA-TKA due to the restoration of the individual's knee kinematics and ligament tension in KA-TKA [14].…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome was Knee Society Score (KSS) 2011 [10], including symptoms (0-25), satisfaction (0-40), expectation (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), and functional activities (0-100) at the 1-year followup. Secondary outcomes included the range of motion (ROM) and the HKA angle.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…indicated KA-TKA could achieve similar kinematics of the patellofemoral joint relative to the normal state [13]. Blakeney et al suggested KA-TKA reproduced more closely normal gait of healthy controls compared to MA-TKA due to the restoration of the individual's knee kinematics and ligament tension in KA-TKA [14].…”
Section: Discussionmentioning
confidence: 99%
“…The main outcome was Knee Society Score (KSS) 2011 [10], including symptom (0-25), satisfaction (0-40), expectation (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and functional activities (0-100) at the 1-year followup. Secondary outcomes included the range of motion (ROM) and HKA angle.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…Thus, several scholars hold the view that KA-TKA may restore normal knee kinematics. Faschingbauer et al indicated KA-TKA could achieve similar kinematics of the patellofemoral joint relative to the normal state [13]. Blakeney et al suggested KA-TKA reproduced more closely normal gait of healthy controls compared to MA-TKA due to the restoration of the individual's knee kinematics and ligament tension in KA-TKA [14].…”
Section: Discussionmentioning
confidence: 99%